Giả sử : \(\sqrt{6}-1>\sqrt{5}\) ⇔ \(\left(\sqrt{6}-1\right)^2>1\) ⇔ \(6-2\sqrt{6}+1>1\)⇔ \(\sqrt{36}-\sqrt{24}>0\) ( Luôn đúng )
KL : Vậy : \(\sqrt{6}-1>\sqrt{5}\)
Giả sử: \(\sqrt{5}< \sqrt{6}-1\Rightarrow\left(\sqrt{5}\right)^2< \left(\sqrt{6}-1\right)^2\)
\(\Rightarrow7-2\sqrt{6}-5>0\Rightarrow2-2\sqrt{6}>0\) vô lí( vì \(\sqrt{4}< \sqrt{24}\))
Vậy \(\sqrt{5}>\sqrt{6}-1\)
Ta có \(\left(\sqrt{5}\right)^2=5\)
\(\left(\sqrt{6}-1\right)^2=6-2\sqrt{6}+1=7-2\sqrt{6}=5+2-2\sqrt{6}\)
Ta có 4<24⇒\(\sqrt{4}< \sqrt{24}\Rightarrow2< 2\sqrt{6}\Rightarrow2-2\sqrt{6}< 0\Rightarrow5+2-2\sqrt{6}< 5\Rightarrow6-2\sqrt{6}+1< 5\Rightarrow\sqrt{6-2\sqrt{6}-1}< \sqrt{5}\Rightarrow\sqrt{6}-1< \sqrt{5}\)
Giả sử √5 > √6 -1 ⇔ √52>√62 ⇔ 5>6(BDT sai)
Vậy √5<√6